2019
DOI: 10.1093/jue/juz012
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting canine fecal and parasitic contamination of public green spaces of Buenos Aires city, Argentina, and visitors’ perception of such contamination

Abstract: Canine fecal contamination in public green areas is difficult to control. Our objectives were to assess: (i) the relationship between fecal contamination in public green spaces of Buenos Aires (Argentina) and the type of green space (boulevard/square/park), considering their area, presence/absence of control measures, and human population density in the surroundings (high or low); (ii) the perception of people of such contamination and (iii) the frequency of parasites in dog feces. In each green space (n = 26)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
8
0
2
Order By: Relevance
“…In Latin America, parasitological analysis of pet feces collected from public spaces in urban areas showed 37.0% to 100.0% of these to be positive for a wide range of intestinal parasites. 8,13,22,[36][37][38][39][40] Similarly, fecal samples collected in Nigeria had a parasite prevalence of 43.3%, and a prevalence of 78.9% was found in Malaysia. 10,41 A more recent study reported a prevalence of 19.1% in stool samples collected in urban streets and farms in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Latin America, parasitological analysis of pet feces collected from public spaces in urban areas showed 37.0% to 100.0% of these to be positive for a wide range of intestinal parasites. 8,13,22,[36][37][38][39][40] Similarly, fecal samples collected in Nigeria had a parasite prevalence of 43.3%, and a prevalence of 78.9% was found in Malaysia. 10,41 A more recent study reported a prevalence of 19.1% in stool samples collected in urban streets and farms in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Second, besides the dispersal of potentially pathogenic microorganisms, inadequate pet feces disposal leading to the spread of zoonotic parasites in urban areas has more and more been shown to be a legitimate concern. [3][4][5][6][7][8][9][10][11][12][13] Overall, public spaces including gardens, streets, roadways, and sidewalks are common sites of animal fecal contamination. Furthermore, public squares, playgrounds, parks, and sandpits may be important sources for pet-borne parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most urban environments, it is common to see that people go to public green spaces for their dogs to defecate there. Since the dog owners do not usually pick up the faeces of their dogs or deworm their dogs periodically, green spaces have become an important source of infective stages for the transmission of canine parasites, some of which have zoonotic potential (Rubel & Wisnivesky, 2010; Wang et al ., 2012; Smith et al ., 2014; Ferreira et al ., 2017; Rubel et al ., 2019). In Argentina, 92% of the population lives in cities (Clarín Newspaper, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The canine faecal contamination and the prevalence of parasites in the faeces in public spaces such as sidewalks and green spaces have been found to be related to the human density (HD) (Rubel & Wisnivesky, 2005, 2010; Rinaldi et al ., 2006; Veneziano et al ., 2006; Rubel et al ., 2019). It seems clear that the risk of parasitic transmission both between dogs and between dogs and humans increases as canine faecal contamination in public spaces increases (Uga, 1993; Mizgajska-Wiktor & Uga, 2006; Poglayen & Marchesi, 2006; Morgan et al ., 2013; Otero et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%